Produktivitas Penangkapan Ikan Menggunakan Purse Seine Berdasarkan Perubahan Fase Bulan Di Kabupaten Bulukumba - Caronge, Siti Adinda Dihar Indahwati; Palo, Mahfud; Nelwan, Alfa F.P.; Wiharto, Muhammad (Jurnal Pendidikan Teknologi Pertanian, 2024)
Purse seine productivity is related to the ability of fishing gear to catch fish that are clustered in the waters and the distribution of pelagic fish in the waters depends on changes in the moon phases that occur. Thus, this research aims to determine the productivity of fishing using purse seines based on changes in lunar phases in Bulukumba Regency. This research was conducted in Bulukumba Regency from July to September 2020. Data was collected by participating in 28 direct fishing trips. The research data used is primary data, namely the type and number of catches grouped based on lunar phases, namely dark, dark to light, light and light to dark periods. Secondary data used are the results of interviews with fishermen and literature studies. The research results showed that there were eight types of fish species caught during the research (scad, mackerel, yellowstripe trevally, frigate tuna, pinkear emperor, barred garfish, rainbow runner, and squid). The three dominant fish caught in each lunar phase were scad (Decapterus spp) with a total of 2.582 kgs, mackerel (Rastrelliger sp) total 1.651 kgs, and yellowstripe trevally (Selaroides sp) total 1.476 kgs. The highest productivity occurred in the second haul during the dark moon period at 0.64 kg/minute and there were no real differences in catch based on moon phase.